Comparative study between intralesional Dexamethasone and oral Prednisolone in the treatment of Infantile Hemangioma (Journal of Paediatric Surgeons of Bangladesh, 2015)
Background: Infantile Hemangioma (IH) is one of the most common childhood neoplasm. Current treatments for children with endangering Infantile Hemangioma are limited, and include primarily oral corticosteroid which has many systemic adverse effects. Furthermore, approximately one third of IH does not respond to oral steroids, prompting active investigations for new treatments.Objective: To compare the efficacy, side effects, and influencing factors of oral Prednisolone and intralesional Dexamethasone (IL) in treatment of IH and thus to find out an effective, cheap and safe modality of treatment for this anomaly.Materials and Methods: This study was carried out on 48 patients of IH with the age range from 1 day to 12 years. Group A (n1=26) patients were treated by oral Prednisolone and group B (n2=22) patients were treated by IL Dexamethasone .Periorbital Hemangioma and IH >54 cubic centimeter were excluded. Therapeutic response of Prednisolone and Dexamethasone was graded as excellent, good, poor and no response. We monitored volume of the lesion and its color change to evaluate the response to treatment.Results: Overall therapeutic responses were 69.2% in Group A and 68.2% in group B. Side effects were noted in 65.4% patient of group A and 36.4% patient of group B. In group A, the commonest (38.5%) side effect was excessive weight gain with cushingoid facies and in group B, commonest (27.3%) side effect was ulceration at injection site. Side effects were more in children of group A. Range of treatment was 4-20 weeks in group A and in group B, it was 4-24 weeks.Conclusion: IL Dexamethasone is effective as oral Prednisolone for treatment of IH .Unlike Prednisolone, IL Dexamethasone is devoid of systemic side effects.J. Paediatr. Surg. Bangladesh 5(1): 12-19, 2014 (January)